Japanese encephalitis in small-scale pig farming in rural Cambodia: Pig seroprevalence and farmer awareness - Henriksson, E.; Söderberg, R.; Ström Hallenberg, G.; Kroesna, K.; Ly, S.; Sear, B.; Unger, Fred; Tum, S.; Hung Nguyen-Viet; Lindahl, Johanna F. (MDPI, 2021)
Japanese encephalitis (JE) is endemic in Cambodia, but circulation of JE virus (JEV) among domestic pigs has previously only been studied in the southern part of the country. The main purpose of this study was to determine the seroprevalence of JEV antibodies in smallholder pigs held in rural areas of Kampong Thom, Preah Vihear, Ratanakiri, and Stung Treng provinces, northeastern Cambodia. Another purpose was to identify possible associations between serologic status and other factors, such as reproductive disorders, and to investigate the farmers’ knowledge of mosquito-borne diseases and use of preventive measures. In October 2019, 139 households were visited throughout the study area, and 242 pigs were sampled for blood. The sera were analysed with ELISA for JEV antibodies. Household representatives were interviewed, and data were recorded for each sampled pig. The apparent seroprevalence was 89.1% in pigs between 3 and 6 months of age, and 100% in pigs over 6 months of age. In total, 93.0% of the pigs tested positive. Province appeared to be the only factor significantly associated with serologic status (p < 0.001). Almost all (97.8%) respondents knew that mosquitos could transmit diseases, and 70.5% had heard of JE. However, only one respondent knew that JEV is transmitted to people through mosquito bites. Very few respondents knew that pigs can become infected with JEV, and no one knew that mosquitos transmit the virus. All families used some sort of mosquito protection for themselves, but only 15.1% protected their pigs from mosquito bites. The children were vaccinated against JE in 93 households, while adults only were vaccinated in eight households. The results suggest that JEV transmission is intense in northeastern Cambodia, and that people’s knowledge about the transmission route of JEV and the role of pigs in the transmission cycle is low. Fortunately, people are well aware of mosquito-borne diseases in general and use mosquito protection, and many children are vaccinated against JE. Nonetheless, it is important that national vaccination is continued, and that people—especially in rural areas where pigs are commonly kept—are educated on the ecology and transmission of JEV.